Transformasi Kesadaran Menjadi Aksi: Strategi Komunikasi BNN Kota Surakarta dalam Program P4GN untuk Generasi Muda - Ilham Yoga Pratama; Hasbullah Azis; Rahmat Wisudawanto (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2026)
Public communication in efforts to prevent drug abuse faces increasingly complex challenges in the digital era, particularly in reaching young people who are strongly influenced by social media and the dynamics of their social environment. This study aims to analyze the communication strategies implemented by the National Narcotics Agency (BNN) of Surakarta City in carrying out the Drug Abuse Prevention, Eradication, and Illicit Trafficking Program (P4GN) oriented toward the younger generation. The study employs a descriptive qualitative approach, with data collected through in-depth interviews with public relations staff of BNN Surakarta City, as well as a review of program documents and communication materials. The data were analyzed using content analysis and validated through source and method triangulation. The findings indicate that BNN’s communication strategies include audience segmentation based on age and educational level, the utilization of digital media such as Instagram and TikTok, and collaboration with local public figures, micro-influencers, and youth communities. Peer-based and participatory communication approaches are considered more effective than one-way, purely informative communication patterns. Nevertheless, limitations in human resources and budget, along with the rapid flow of digital information, remain the main challenges in program implementation. This study emphasizes the importance of persuasive, adaptive, and contextual communication strategies to enhance the effectiveness of P4GN campaigns among the younger generation.